KETEPATAN WAKTU APLIKASI Paecilomyces lilacinus DALAM MENGENDALIKAN NEMATODA BENGKAK AKAR (Meloidogyne spp.) PADA TANAMAN TOMAT - Winarto Winarto; Darnetty Darnetty; Yenny Liswarni (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2020)
Root-knot nematodes (Meloidogyne spp.) have been reported to be one of the primary pathogens that decreased tomato production in Indonesia. Biological control of root-knot nematodes by using parasitic fungus as like as Paecilomyces lilacinus is still limited. An effective application of parasitic fungi could be successful by managing a suitability application time. The study aimed to determine the suitability of the application time of the P.lilacinus in controlling root-knot nematodes on tomato. The study was conducted in farmers' land that was infected by root-knot nematodes. The experiment was done in a randomized block design with applying P.lilacinus isolates on 12, 8, and 4 days before planting, planting time, and 4, 8, 12 days after planting. All treatments were repeated four times. The application of P. lilacinus onto tomato root at planting time was better at suppressing the development of root-knot nematode compared to applications made before or after planting. P. lilacinus was able to suppress the number of root-knot (66.08%), the number of egg groups (77.33%), the number of eggs (26.79%), and the number of nematodes in the soil (82.20%). Keywords: Application time, Meloidogyne spp., Paecilomyces lilacinus, tomato